Conservative Management of a Large Periapical Lesion Using Decompression Technique: A Case Report - Mehdizadeh, Amir Hosein; Soltani Nejad, Fateme; yousefi, Motahareh; Sadeghi, Razieh; Shahravan, Arash (Iranian Endodontic Journal, 2025)
The management of extensive periapical lesions poses a significant challenge in endodontic therapy due to their potential cystic nature, anatomical proximity to critical structures, risk of cortical perforation, and complex infection dynamics. This report presents a successful case of a large through-and-through periapical lesion managed conservatively via decompression. Initial periapical radiographs revealed poor-quality root canal therapy and a large radiolucent lesion associated with a maxillary lateral incisor. Cone-beam computed tomography (CBCT) imaging confirmed a through-and-through lesion approximately 12 × 9.5 × 10.5 mm in size. Based on the clinical and radiographic features, pulpal diagnosis was previous endodontic treatment with an infected root canal system and the periapical diagnosis was a radicular cyst; however, a definitive diagnosis would have required a serial sectioning biopsy, which was not feasible under the present circumstances. Initial non-surgical retreatment as the first treatment choice, with multiple intracanal medicament replacements, proved ineffective due to persistent discharge of the canal. Furthermore, surgical intervention was deemed high-risk due to the lesion’s proximity to the incisive foramen, palatal mucosa, sinus floor, and nasal cavity. Decompression, a minimally invasive technique with low morbidity, was selected. Following drainage, a drain was inserted via the thinnest cortical plate, and daily irrigation was initiated. The lesion was monitored every two weeks, with progressive reduction in size documented radiographically. After 5 months, the root canal was obturated and the tooth was restored by composite resin due to the cessation of drainage. The drain was removed at 6 months, and by the 9-month follow-up, significant bone regeneration was evident radiographically. The tooth was asymptomatic, exhibited no mobility or sensitivity to percussion or palpation, and periodontal probing revealed no pathologic pockets.